Method for preparing composite iron-based polyanion positive electrode material
The composite iron-based polyanionic cathode material Na4Fe3(PO4)2(P2O7)@C&MXenes was prepared through sand milling and spray drying, which solved the improvement space for NFPP in terms of energy density, rate performance and cycle life, and achieved significant improvement in battery performance and applicability in large-scale energy storage.
Patent Information
- Application Number
- CN202411592748.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-11-08
AI Technical Summary
The existing sodium ion battery cathode material NFPP still has room for improvement in energy density, rate performance and cycle life, and it is difficult to achieve large-scale production and wide application.
The sodium source, ferrous source, phosphorus source, carbon source and MXenes were dispersed evenly in solvent water by sand milling and spray granulation, and then sintered under an inert atmosphere to prepare the composite iron-based polyanionic cathode material Na4Fe3(PO4)2(P2O7)@C&MXenes.
It improves the electrochemical activity and stability of NFPP, improves the energy density, power density and cycle life of the battery, and enhances the safety of the battery, making it suitable for applications in the field of large-scale energy storage.
Smart Images

Figure CN119637832A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of sodium ion battery positive electrode material preparation, and in particular relates to a method for preparing a composite iron-based polyanion positive electrode material. Background Art
[0002] At present, the sodium-ion battery industry is in the early stages of commercialization, and it is particularly important to find battery materials suitable for industrialization. As the core component of sodium-ion batteries, positive electrode materials have an important impact on key indicators such as battery energy density and cycle life.
[0003] The three mainstream positive electrode materials for sodium-ion batteries are layered oxides, Prussian blue (white) compounds, and polyanion compounds. Layered oxides are sensitive to air and will produce irreversible phase changes during chemical reactions, which will have a serious impact on the cycle stability of the battery; the coordinated water in the Prussian blue (white) lattice is difficult to remove, which seriously affects the capacity and cycle performance of the battery; and polyanion compounds have attracted widespread attention due to their advantages such as high operating voltage, good thermal stability, and good cycle life. In particular, the iron-based polyanion positive electrode material Na4Fe3(PO4)2(P2O7) (hereinafter referred to as NFPP), because it has both (PO4) 3- The stable framework structure and (P2O7) 4- The high working potential brought by the inductive effect and the ability to achieve three-electron transfer give it the advantages of long cycle life, high working voltage and high theoretical specific capacity, and it is expected to be applied in the field of large-scale energy storage.
[0004] The preparation methods of iron-based polyanion positive electrode material NFPP include high temperature solid phase method, carbon thermal reduction method, sol-gel method, hydrothermal synthesis method, liquid phase coprecipitation method, etc. Among them, the high temperature solid phase method is one of the most common and mature methods. Ferrous iron source is used as the main iron source, and then sodium source and phosphorus source are added, fully ground and sintered to prevent Fe 2+ Oxidized to Fe 3+ During the sintering process, inert gas is continuously introduced, and a small amount of hydrogen is added as a reducing gas. NFPP is obtained after the furnace is cooled. The high-temperature solid-phase method for synthesizing NFPP has the advantages of simple process and suitability for industrialization. However, the current preparation process of NFPP is relatively complicated, and the electrochemical performance of NFPP needs to be improved.
[0005] The patent application with publication number CN118263419A discloses an iron-based polyanion sodium ion battery positive electrode material coated with a Ti3C2 nanosheet and a carbon double layer and a preparation method thereof. The two-dimensional Ti3C2 nanosheet is secondary coated and sintered to form Na4Fe3(PO4)2P2O7@C / Ti3C2. On the one hand, it can improve the electronic conductivity of the material, and on the other hand, it can effectively prevent the material from agglomerating during the drying and sintering process, accelerate ion transmission, and obtain the sodium iron pyrophosphate positive electrode material with better performance.
[0006] The patent application with publication number CN118083938A discloses a method for preparing sodium ferric pyrophosphate with flexible adjustment of compaction and electrical properties. It adopts two different iron sources and a process of multi-stage sand grinding followed by spray drying, which shortens the sand grinding time and reduces production energy consumption, while achieving a comprehensive improvement in the compaction density and electrical properties of sodium ferric pyrophosphate.
[0007] However, the energy density, rate performance and cycle life of sodium-ion batteries using NFPP as the positive electrode material still need to be improved, and large-scale production and widespread application of NFPP cannot be achieved. Summary of the invention
[0008] The present invention aims at the above-mentioned technical problems existing in the prior art and provides a method for preparing a composite iron-based polyanion positive electrode material, which comprises the following steps:
[0009] (1) adding a sodium source, a ferrous source, a phosphorus source, a carbon source and MXenes to solvent water and dispersing them uniformly to obtain a slurry, wherein the sodium source, the ferrous source and the phosphorus source are basic raw materials for synthesizing materials, and the carbon source and MXenes are raw materials for composite coating;
[0010] (2) Place the mixed slurry in a sand mill and grind it thoroughly to obtain a particle size of D 50 Controlled between 200-400nm;
[0011] (3) transferring the ground slurry into a spray dryer for spray granulation to obtain a precursor powder;
[0012] (4) Sintering the precursor powder under an inert atmosphere to obtain the composite iron-based polyanion positive electrode material.
[0013] The carbon source in step (1) includes iron-nickel doped polyethylene glycol, and its preparation method is as follows:
[0014] K1: Mix 0.5-2 parts of ferric nitrate, 7-12 parts of 2,5-dimercaptoterephthalic acid and 300-400 parts of ethanol, heat to 40-50°C, and react for 100-150 minutes;
[0015] K2: Add 0.05-0.5 parts of allyl(cyclopentadienyl)nickel and 2-6 parts of sodium ethoxide, raise the temperature to 60-70°C, and react for 60-120 minutes;
[0016] K3: Add 50-70 parts of allyl polyethylene glycol, react at 60-70° C. for 100-150 minutes, and distill off ethanol after the reaction to obtain the iron-nickel doped polyethylene glycol.
[0017] Preferably, the sodium source in step (1) is one or more of sodium pyrophosphate, sodium dihydrogen phosphate, disodium hydrogen phosphate, sodium carbonate and sodium oxalate.
[0018] Preferably, the ferrous source in step (1) is one or more of ferrous phosphate octahydrate, ferrous oxalate dihydrate, ferrous pyrophosphate and ferrous acetate.
[0019] Preferably, the phosphorus source in step (1) is one or more of sodium pyrophosphate, sodium dihydrogen phosphate, disodium hydrogen phosphate, ammonium dihydrogen phosphate, ferrous phosphate octahydrate and ferrous pyrophosphate.
[0020] Preferably, in step (1), MXenes is a transition metal carbonitride, which is one or more of Ti3C2, Ti3CN, Nb2C, Mo2C2 and V3C2, preferably Ti3CN.
[0021] Preferably, in step (1), the molar ratio of the sodium element in the sodium source, the ferrous element in the ferrous source, and the phosphorus element in the phosphorus source is 4:3:4, the iron-nickel doped polyethylene glycol in the carbon source accounts for 1% of the total weight of the slurry, and the MXenes account for 0.5%-1% of the total weight of the slurry.
[0022] Preferably, the carbon source in step (1) further comprises one or more of glucose, sucrose, citric acid and ascorbic acid, and the carbon source other than the iron-nickel doped polyethylene glycol accounts for 2%-4% of the total weight of the slurry.
[0023] Preferably, the sand mill rotation speed in step (2) is 1500-2500 r / min, and the grinding time is 75-190 min.
[0024] Preferably, the spray drying process parameters in step (3) are as follows:
[0025] The feed rate was 55-70 mL / min, the inlet temperature was 170-210°C, and the outlet temperature was 95-105°C.
[0026] Preferably, in step (4), the sintering method is to first heat to 350°C and keep it for 4-6 hours, and then heat to 500°C and keep it for 10-12 hours. The sintering temperature should not exceed 530°C, otherwise there will be impurities produced, resulting in a decrease in electrical properties; the sintering temperature should not be lower than 480°C, otherwise it will cause the crystallinity of the material to deteriorate.
[0027] Preferably, the molecular weight of the allyl polyethylene glycol in step K3 is 1000-5000Da, more preferably 1000Da, 2000Da, 3400Da and 5000Da.
[0028] The present invention also provides a composite iron-based polyanion positive electrode material prepared by the above method, which is sodium iron pyrophosphate compositely coated with MXenes material and carbonaceous precursor, and its structural formula is expressed as Na4Fe3(PO4)2(P2O7)@C&MXenes.
[0029] The present invention also provides a sodium ion battery, comprising a positive electrode material, an electrolyte, a negative electrode material and a separator, wherein the positive electrode material is the above-mentioned composite iron-based polyanion positive electrode material.
[0030] Compared with the prior art, the advantages of the present invention are:
[0031] (1) The present invention can improve the electrochemical activity and stability of NFPP by doping polyethylene glycol with iron and nickel as a dispersant: after doping with tris(2,5-dimercaptoterephthalate) iron (III) and allyl(cyclopentadienyl) nickel, the introduced -OH / -COOH functional groups can provide more bonding sites for the positive electrode precursor, and generate a reducing atmosphere through pyrolysis during the sintering process, which is beneficial to the synthesis of polyanion materials and the formation of a uniform carbon coating. The obtained composite material has excellent electrochemical properties, structural stability and thermal stability. The application of the composite material as a positive electrode material in sodium ion batteries not only improves the energy density and power density of the battery, but also enhances the cycle life and safety of the battery.
[0032] (2) The sand milling combined with spray drying process adopted in the present invention can make the raw materials dispersed evenly and improve the purity of the sintered material. The XRD test results show that the NFPP prepared by this high-temperature solid phase method is a typical orthorhombic crystal system, Pn21a space group. In the voltage range of 2-4V, the 0.1C discharge capacity can be as high as 102mAh / g. After 50 charge and discharge cycles at a rate of 1C, the discharge capacity is still maintained at 90mAh / g, and the coulomb efficiency is stable at 99.9%. The excellent cycle stability makes it applicable to the field of large-scale energy storage.
[0033] (3) The chemical ratio of sodium, iron and phosphorus in the raw materials used in the present invention is easy to control by batching, and the raw materials are simple and easy to obtain; the process used in the present invention is simple, and the flow is reliable, the process is fast, and it is easy to industrialize production.
[0034] (4) The composite coating technology adopted in the present invention coats the MXenes material onto the material surface by in-situ pyrolysis. On the one hand, the excellent conductivity of the MXenes material is used to improve the electronic conductivity of the positive electrode material, thereby improving the rate performance and cycle performance of the material; on the other hand, the special layered structure of the MXenes material is used to improve the ion transmission rate on the material surface, thereby avoiding the problem of decreased sodium ion transmission rate due to excessively thick conductive layer coating. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 This is a scanning electron microscope image of the NFPP prepared in Example 1 of the present invention.
[0036] Figure 2 This is the XRD pattern of NFPP prepared in Example 1 of the present invention.
[0037] Figure 3 This is a rate charge and discharge curve diagram of the sodium ion battery prepared in Example 1 of the present invention.
[0038] Figure 4 This is a rate charge and discharge curve diagram of the sodium ion battery prepared in Example 2 of the present invention.
[0039] Figure 5 This is a rate charge and discharge curve diagram of the sodium ion battery prepared in Example 3 of the present invention.
[0040] Figure 6 This is a rate charge and discharge curve diagram of the sodium ion battery prepared in Example 4 of the present invention.
[0041] Figure 7 This is a rate charge and discharge curve diagram of the sodium ion battery prepared in Comparative Example 1 of the present invention.
[0042] Figure 8 This is a cycle curve diagram of the sodium ion battery prepared in Example 1 of the present invention at a 1C rate. DETAILED DESCRIPTION
[0043] Example 1
[0044] A method for preparing a positive electrode active material for a sodium ion battery comprises the following steps:
[0045] (1) Weigh 1 mol of sodium pyrophosphate, 1 mol of ferrous phosphate octahydrate, 1% of the total weight of the raw materials, iron-nickel doped polyethylene glycol, 3% of the total weight of the raw materials, and 0.5% of the total weight of the raw materials Ti3CN, and add them to deionized water in turn for dispersion. Among them, sodium pyrophosphate is both a sodium source and a phosphorus source, ferrous phosphate octahydrate is both an iron source and a phosphorus source, and citric acid and Ti3CN are carbonaceous precursors;
[0046] (2) Place the mixed slurry in a sand mill and grind it at a speed of 1500 r / min for 10 min, and at a speed of 2500 r / min for 3 h. Use a particle size analyzer to detect the slurry particle size, and beat out the precursor slurry when it reaches the expected particle size;
[0047] (3) The precursor slurry is poured into a container, the inlet temperature of the spray dryer is set to 170°C, the outlet temperature is maintained between 95°C and 105°C, and the feed rate is 55 mL / min; the fan and heater are turned on in sequence, and the sprayer is turned on after reaching the set temperature. The slurry is continuously stirred during the feeding process until the slurry is completely sprayed, and the precursor powder is collected;
[0048] (4) The precursor powder obtained by spray drying was placed in a nitrogen atmosphere, heated to 350°C at a heating rate of 2°C / min and kept warm for 4 h, and then heated to 500°C at a heating rate of 2°C / min and kept warm for 10 h to obtain Na4Fe3(PO4)2(P2O7)@C&MXenes.
[0049] The preparation method of iron-nickel doped polyethylene glycol in step (1) is:
[0050] K1: Mix 0.5 g of ferric nitrate, 7 g of 2,5-dimercaptoterephthalic acid and 300 g of ethanol, heat to 40°C, and react for 100 minutes;
[0051] K2: Add 0.05 g of allyl(cyclopentadienyl)nickel and 2 g of sodium ethoxide, raise the temperature to 60°C, and react for 60 minutes;
[0052] K3: Add 50 g of allyl polyethylene glycol (the molecular weight of allyl polyethylene glycol is 1000 Da), react at 60° C. for 100 minutes, and remove ethanol by distillation after the reaction to obtain iron-nickel doped polyethylene glycol.
[0053] Example 2
[0054] A method for preparing a positive electrode active material for a sodium ion battery comprises the following steps:
[0055] (1) Weigh 1 mol of sodium pyrophosphate, 3 mol of ferrous oxalate dihydrate, 2 mol of ammonium dihydrogen phosphate, 1% of the total weight of the raw materials, 4% of the total weight of the raw materials, and 0.5% of the total weight of the raw materials, and add them to deionized water for dispersion. Among them, sodium pyrophosphate is both a sodium source and a phosphorus source, ferrous oxalate dihydrate is an iron source, ammonium dihydrogen phosphate is a phosphorus source, and sucrose and Ti3CN are carbonaceous precursors;
[0056] (2) Place the mixed slurry in a sand mill and grind it at a speed of 1500 r / min for 15 min, and at a speed of 2500 r / min for 2.5 h. Use a particle size analyzer to detect the slurry particle size, and beat out the precursor slurry when it reaches the expected particle size;
[0057] (3) The precursor slurry is poured into a container, the inlet temperature of the spray dryer is set to 210°C, the outlet temperature is maintained between 95°C and 105°C, and the feed rate is 70 mL / min; the fan and heater are turned on in sequence, and the sprayer is turned on after reaching the set temperature. The slurry is continuously stirred during the feeding process until the slurry is completely sprayed, and the precursor powder is collected;
[0058] (4) The precursor powder obtained by spray drying was placed in a nitrogen atmosphere, heated to 350°C at a heating rate of 2°C / min and kept warm for 6 h, and then heated to 500°C at a heating rate of 2°C / min and kept warm for 12 h to obtain Na4Fe3(PO4)2(P2O7)@C&MXenes.
[0059] The preparation method of iron-nickel doped polyethylene glycol in step (1) is:
[0060] K1: 0.9 g of ferric nitrate, 9 g of 2,5-dimercaptoterephthalic acid and 330 g of ethanol were mixed, the temperature was raised to 42°C, and the reaction was carried out for 120 minutes;
[0061] K2: Add 0.1 g of allyl(cyclopentadienyl)nickel and 3 g of sodium ethoxide, raise the temperature to 62°C, and react for 80 minutes;
[0062] K3: Add 55 g of allyl polyethylene glycol (the molecular weight of allyl polyethylene glycol is 2000 Da) and react at 62° C. for 120 minutes. After the reaction, remove ethanol by distillation to obtain iron-nickel doped polyethylene glycol.
[0063] Example 3
[0064] A method for preparing a positive electrode active material for a sodium ion battery comprises the following steps:
[0065] (1) Weigh 1 mol of sodium pyrophosphate, 3 mol of ferrous acetate, 2 mol of ammonium dihydrogen phosphate, 1% of the total weight of the raw materials iron-nickel doped polyethylene glycol, 2% of the total weight of the raw materials ascorbic acid and 1% of the total weight of the raw materials Mo2C2, and add them into deionized water in sequence for dispersion. Among them, sodium pyrophosphate is both a sodium source and a phosphorus source, ferrous acetate is an iron source, ammonium dihydrogen phosphate is a phosphorus source, and ascorbic acid and Mo2C2 are carbonaceous precursors;
[0066] (2) Place the mixed slurry in a sand mill and grind it at a speed of 1500 r / min for 15 min, and at a speed of 2200 r / min for 1 h. Use a particle size analyzer to detect the slurry particle size, and beat out the precursor slurry when it reaches the expected particle size;
[0067] (3) The precursor slurry is poured into a container, the inlet temperature of the spray dryer is set to 180°C, the outlet temperature is maintained between 95°C and 105°C, and the feed rate is 55 mL / min; the fan and heater are turned on in sequence, and the sprayer is turned on after reaching the set temperature. The slurry is continuously stirred during the feeding process until the slurry is completely sprayed, and the precursor powder is collected;
[0068] (4) The precursor powder obtained by spray drying was placed in a nitrogen atmosphere, heated to 350°C at a heating rate of 2°C / min and kept warm for 6 h, and then heated to 500°C at a heating rate of 2°C / min and kept warm for 10 h to obtain Na4Fe3(PO4)2(P2O7)@C&MXenes.
[0069] The preparation method of iron-nickel doped polyethylene glycol in step (1) is:
[0070] K1: Mix 1g of ferric nitrate, 10g of 2,5-dimercaptoterephthalic acid and 370g of ethanol, heat to 48°C, and react for 140 minutes;
[0071] K2: Add 0.4 g of allyl(cyclopentadienyl)nickel and 5 g of sodium ethoxide, raise the temperature to 68°C, and react for 100 minutes;
[0072] K3: Add 67 g of allyl polyethylene glycol (the molecular weight of allyl polyethylene glycol is 3400 Da), react at 66° C. for 130 minutes, and remove ethanol by distillation after the reaction to obtain iron-nickel doped polyethylene glycol.
[0073] Example 4
[0074] A method for preparing a positive electrode active material for a sodium ion battery comprises the following steps:
[0075] (1) Weigh 4 mol of sodium dihydrogen phosphate, 3 mol of ferrous oxalate dihydrate, 1% of the total weight of the raw materials, 4% of the total weight of the raw materials, and 1% of the total weight of the raw materials, and add them to deionized water for dispersion. Among them, sodium dihydrogen phosphate is both a sodium source and a phosphorus source, ferrous oxalate dihydrate is an iron source, ammonium dihydrogen phosphate is a phosphorus source, and sucrose and Mo2C2 are carbonaceous precursors.
[0076] (2) Place the mixed slurry in a sand mill and grind it at a speed of 1500 r / min for 15 min, and at a speed of 2500 r / min for 2.5 h. Use a particle size analyzer to detect the slurry particle size, and beat out the precursor slurry when it reaches the expected particle size.
[0077] (3) The precursor slurry is poured into a container, the inlet temperature of the spray dryer is set to 200°C, the outlet temperature is maintained between 95 and 105°C, and the feed rate is 65 mL / min; the fan and heater are turned on in sequence, and the sprayer is turned on after the set temperature is reached. The slurry is continuously stirred during the feeding process until the slurry is completely sprayed, and the precursor powder is collected.
[0078] (4) The precursor powder obtained by spray drying was placed in a nitrogen atmosphere, heated to 350°C at a heating rate of 2°C / min and kept warm for 6 h, and then heated to 500°C at a heating rate of 2°C / min and kept warm for 10 h to obtain Na4Fe3(PO4)2(P2O7)@C&MXenes.
[0079] The preparation method of iron-nickel doped polyethylene glycol in step (1) is:
[0080] K1: Mix 2g of ferric nitrate, 12g of 2,5-dimercaptoterephthalic acid and 400g of ethanol, heat to 50°C, and react for 150 minutes;
[0081] K2: Add 0.5 g of allyl(cyclopentadienyl)nickel and 6 g of sodium ethoxide, raise the temperature to 70°C, and react for 120 minutes;
[0082] K3: Add 70 g of allyl polyethylene glycol (the molecular weight of allyl polyethylene glycol is 5000 Da) and react at 70° C. for 150 minutes. After the reaction, remove ethanol by distillation to obtain iron-nickel doped polyethylene glycol.
[0083] Comparative Example 1
[0084] A method for preparing a positive electrode active material for a sodium ion battery comprises the following steps:
[0085] (1) Weigh 1 mol of sodium pyrophosphate, 3 mol of ferrous oxalate dihydrate, 2 mol of ammonium dihydrogen phosphate, 1% of the total weight of the raw materials, 4% of the total weight of the raw materials, and 0.5% of the total weight of the raw materials Ti3CN, and add them into deionized water in sequence for dispersion. Among them, sodium pyrophosphate is both a sodium source and a phosphorus source, ferrous oxalate dihydrate is an iron source, ammonium dihydrogen phosphate is a phosphorus source, and sucrose and Ti3CN are carbonaceous precursors.
[0086] (2) Place the mixed slurry in a sand mill and grind it at a speed of 1500 r / min for 15 min, and at a speed of 2500 r / min for 3 h. Use a particle size analyzer to detect the slurry particle size, and beat out the precursor slurry when it reaches the expected particle size.
[0087] (3) The precursor slurry is poured into a container, the inlet temperature of the spray dryer is set to 210°C, the outlet temperature is maintained between 95 and 105°C, and the feed rate is 70 mL / min; the fan and heater are turned on in sequence, and the sprayer is turned on after the set temperature is reached. The slurry is continuously stirred during the feeding process until the slurry is completely sprayed, and the precursor powder is collected.
[0088] (4) The precursor powder obtained by spray drying was placed in a nitrogen atmosphere, heated to 350°C at a heating rate of 2°C / min and kept warm for 6 h, and then heated to 500°C at a heating rate of 2°C / min and kept warm for 12 h to obtain Na4Fe3(PO4)2(P2O7)@C&MXenes.
[0089] Test Example 1
[0090] Test conditions:
[0091] The NFPP prepared in Example 1-4 was used as the positive electrode active material of the sodium ion battery, mixed with the conductive agent SP and the binder PVDF in a mass ratio of 90:5:5, and the current collector was aluminum foil to form the positive electrode; the metal sodium sheet was used as the negative electrode of the sodium ion electrode, the glass fiber was used as the diaphragm, and the 1mol / LNaClO4 EC / DMC (volume ratio 1:1) + 5% FEC solution was used as the electrolyte. The battery was assembled in a glove box with an oxygen partial pressure of less than 0.01PPM, a water partial pressure of less than 0.01PPM, and an argon atmosphere. The constant current and constant voltage charging-constant current discharge mode was used, the voltage range was 2-4V, and the charge and discharge test was carried out at a current density of 0.1C-0.2C-0.5C-1C.
[0092] Figure 1 This is a scanning electron microscope image of the NFPP prepared in Example 1 of the present invention. It can be seen from the figure that the particle morphology is spherical, the sample particle size is 5-45μm, and the particle surface is rough. The high-magnification magnification image shows that the particle morphology is relatively uniform and has obvious scaly substances, and the composite coating effect on the particle surface is acceptable.
[0093] Figure 2 The XRD diagram of the NFPP prepared in Example 1 of the present invention is shown in Figure 1. The crystal structure of the material was analyzed by X-ray diffraction test. The results show that the diffraction peaks of the NFPP composite phase exist at 9.8°, 15.8°, 16.7°, 32.1°, and 33.6°, which correspond to the (200), (011), (210), (022), and (222) crystal planes of the material, respectively. The XRD results prove that the material synthesized by this formulation process is indeed pure phase.
[0094] Figure 3 The figure is a rate charge and discharge curve of the sodium ion battery prepared in Example 1 of the present invention. The sample can provide a discharge specific capacity of 102 mAh / g, 99 mAh / g, 97 mAh / g, and 94 mAh / g at a rate of 0.1C, 0.2C, 0.5C, and 1C, respectively, and the 1C capacity retention rate is 92%.
[0095] Figure 4 The figure is a rate charge and discharge curve of the sodium ion battery prepared in Example 2 of the present invention. The sample can provide a discharge specific capacity of 97 mAh / g, 95 mAh / g, 93 mAh / g, and 90 mAh / g at rates of 0.1C, 0.2C, 0.5C, and 1C, respectively, and the 1C capacity retention rate is 93%.
[0096] Figure 5 The figure is a rate charge and discharge curve of the sodium ion battery prepared in Example 3 of the present invention. The sample can provide a discharge specific capacity of 81 mAh / g, 79 mAh / g, 75 mAh / g, and 70 mAh / g at rates of 0.1C, 0.2C, 0.5C, and 1C, respectively, and the 1C capacity retention rate is 86%.
[0097] Figure 6 The figure is a rate charge and discharge curve of the sodium ion battery prepared in Example 4 of the present invention. The sample can provide a discharge specific capacity of 87 mAh / g, 85 mAh / g, 82 mAh / g, and 79 mAh / g at rates of 0.1C, 0.2C, 0.5C, and 1C, respectively, and the 1C capacity retention rate is 91%.
[0098] Figure 7 The figure is a rate charge and discharge curve of the sodium ion battery prepared in Comparative Example 1 of the present invention. The sample can provide a discharge specific capacity of 91 mAh / g, 90 mAh / g, 88 mAh / g, and 85 mAh / g at rates of 0.1C, 0.2C, 0.5C, and 1C, respectively, and the 1C capacity retention rate is 93%.
[0099] Figure 8The graph is a 50-cycle curve of the sodium ion battery prepared in Example 1 of the present invention at a 1C rate. After 50 charge and discharge cycles at a 1C rate, the discharge capacity is still maintained at 90 mAh / g, and the coulombic efficiency is stable at 99.9%, indicating that the material has excellent cycle stability.
[0100] Compared with Example 2, Comparative Example 1 of the present invention uses undoped polyethylene glycol as a dispersant. Finally, the discharge specific capacity of the sodium ion battery prepared in Comparative Example 1 is lower than that in Example 2. It can be seen that the doping scheme adopted in the present invention can improve the electrochemical properties of NFPP.
Claims
1. A method for preparing a composite iron-based polyanion positive electrode material, characterized in that: The steps include: (1) adding a sodium source, a ferrous source, a phosphorus source, a carbon source and MXenes to solvent water and dispersing them uniformly to obtain a slurry; (2) Place the mixed slurry in a sand mill and grind it thoroughly to obtain a particle size of D 50 Controlled between 200-400nm, (3) The ground slurry is transferred to a spray dryer for spray granulation to obtain a precursor powder. (4) sintering the precursor powder under an inert atmosphere to obtain the composite iron-based polyanion positive electrode material; The carbon source in step (1) includes iron-nickel doped polyethylene glycol, and its preparation method is as follows: K1: Mix 0.5-2 parts of ferric nitrate, 7-12 parts of 2,5-dimercaptoterephthalic acid and 300-400 parts of ethanol, heat to 40-50°C, and react for 100-150 minutes. K2: Add 0.05-0.5 parts of allyl(cyclopentadienyl)nickel and 2-6 parts of sodium ethoxide, raise the temperature to 60-70°C, and react for 60-120 minutes. K3: Add 50-70 parts of allyl polyethylene glycol, react at 60-70° C. for 100-150 minutes, and distill off ethanol after the reaction to obtain the iron-nickel doped polyethylene glycol.
2. The method for preparing a composite iron-based polyanion positive electrode material according to claim 1, characterized in that: The sodium source in step (1) is one or more of sodium pyrophosphate, sodium dihydrogen phosphate, disodium hydrogen phosphate, sodium carbonate and sodium oxalate, The ferrous iron source is one or more of ferrous phosphate octahydrate, ferrous oxalate dihydrate, ferrous pyrophosphate and ferrous acetate, The phosphorus source is one or more of sodium pyrophosphate, sodium dihydrogen phosphate, disodium hydrogen phosphate, ammonium dihydrogen phosphate, ferrous phosphate octahydrate and ferrous pyrophosphate, The MXenes are one or more of Ti3C2, Ti3CN, Nb2C, Mo2C2 and V3C2; In step (1), the molar ratio of the sodium element in the sodium source, the ferrous element in the ferrous source, and the phosphorus element in the phosphorus source is 4:3:4, the iron-nickel doped polyethylene glycol in the carbon source accounts for 1% of the total weight of the slurry, and the MXenes account for 0.5%-1% of the total weight of the slurry.
3. The method for preparing a composite iron-based polyanion positive electrode material according to claim 1, characterized in that: The carbon source in step (1) further comprises one or more of glucose, sucrose, citric acid and ascorbic acid; The carbon source other than the iron-nickel doped polyethylene glycol accounts for 2%-4% of the total weight of the slurry.
4. The method for preparing a composite iron-based polyanion positive electrode material according to claim 1, characterized in that: The sand mill speed in step (2) is 1500-2500 r / min, and the grinding time is 75-190 min.
5. The method for preparing a composite iron-based polyanion positive electrode material according to claim 1, characterized in that: The spray drying process parameters in step (3) are as follows: The feed rate was 55-70 mL / min, the inlet temperature was 170-210°C, and the outlet temperature was 95-105°C.
6. The method for preparing a composite iron-based polyanion positive electrode material according to claim 1, characterized in that: In step (4), the sintering method is to first heat to 350°C and keep it warm for 4-6 hours, and then heat to 500°C and keep it warm for 10-12 hours.
7. The method for preparing a composite iron-based polyanion positive electrode material according to claim 1, characterized in that: The molecular weight of the allyl polyethylene glycol in step K3 is 1000-5000 Da.
8. A composite iron-based polyanion positive electrode material prepared by the method according to any one of claims 1 to 7.
9. A sodium ion battery comprising a positive electrode material, an electrolyte, a negative electrode material and a separator, characterized in that: The positive electrode material is the composite iron-based polyanion positive electrode material according to claim 8.
Citation Information
Patent Citations
Preparation method of conductive modified lithium iron phosphate
CN102683698A
Positive electrode material for sodium-ion battery and preparation method thereof
CN108046231A
Aluminum atom doped PEG-based polymer electrolyte and preparation method and application thereof
CN116053701A
Preparation method of high-capacity lithium iron manganese phosphate positive electrode material
CN116682962A
Carbon-coated modified polyanionic positive electrode material as well as preparation method and application thereof
CN116960308A
Cited By
Preparation method and application of ferric sodium pyrophosphate positive electrode composite material
CN121044561A
Modified lithium iron phosphate positive electrode material, preparation method and application thereof
CN122501843A
Modified lithium iron phosphate positive electrode material, preparation method and application thereof
CN122501843B
Preparation method for composite iron-based polyanion positive electrode material
WO2026098603A1